Analisis Faktor Yang Mempengaruhi Pengunjung Objek Wisata Kawah Ijen Banyuwangi - RIA NURMALASARI, TUS (Jurnal Pendidikan Tata Niaga (JPTN), 2016)
Kawah ijen that is one tourist attraction banyuwangi example tourism has grown in banyuwangi. kawah ijen already known for a long time by travelers domestic and foreign. Strategy used by tourism objects kawah ijen are varied as advertising, personal sales, and public relations ( public relations ). Every year the number of tourists better local tourists and foreign tourists. In this research the number of subjects is 32 variable, the number of sample who would check 32 x 5 = 160 respondents. The research results show that value kmo 0,752, this indicates that the use of analysis factor right. As many as 32 variables that were used in this research, obtained the results of seven of the reduction of that can have value eigenvalue & gt; 1 , which indicates that there are seven of that could affect the visitors tourist attraction kawah ljen banyuwangi. Factor 1 is factor play with a large percentage of 19,830 % variance , factor 2 is factor self fulfilment with a large percentage of 17,534 % variance , factor is age 3 factor with a large percentage of 15,156 % variance , 4 factor is factor knowledge with a large percentage of 12,969 % variance , 5 factor is factor personal influence with a large percentage of 11,113 % variance , 6 factor is a factor with a large percentage of 9,707 % variance , 7 factor is factor the number of those with a large percentage of 7,868 % variance. Thus factor that has an effect the main in visitors tourism objects kawahijen banyuwangi is factor play with the 19,830 %. Keywords: Analysis Factors, Kawah Ijen, tourist attraction